GODAN Action: digital capacity building - Msengezi, Chipo (Technical Centre for Agricultural and Rural Cooperation, 2019)
Increased availability of agricultural data could help overcome key challenges for the sector, however many stakeholders still struggle to access and interpret agridata. GODAN's Action project aims to tackle this issue.